Effect of thermodynamically metastable components on mechanical and oxidation properties of the thermal-sprayed MoSi2 based composite coating. (15th July 2019) - Sun, Jia; Li, Tao; Zhang, Guang-Peng
Highlights: MoSi2 based composite coatings with thermodynamically metastable components were produced by supersonic plasma spraying. Annealing treatment can eliminate the metastable components in as-sprayed MoSi2 based composite coatings. The highest indentation fracture toughness of as-sprayed coatings was derived from the metastable components' toughening. The metastable components can provide quick oxidation protection abilities upon high temperature service. Abstract: Thermodynamically metastable components in plasma-sprayed MoSi2 based composite coatings were comparatively investigated to reveal their impacts on mechanical performance and oxidation behavior of the free-standing coatings. Metastable components have positively contributed to the improved mechanical and anti-oxidation properties of the as-sprayed coatings. The amorphous domain and nano-Mo phases could be regarded as the reinforcements in terms of the indentation fracture toughness. Upon high-temperature exposure in air, metastable components would be sacrificed by facilitating the better formation of surface protective scale due to the β → α transformation as well as volatilization of the gaseous Mo-oxides.